IMPLEMENTASI AKAD MURABAHAH PADA PEMBIAYAAN DI BPRS ALWADIAH TASIKMALAYA - Dita Ardita; Rangga Munggaran (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
An abstranct is a brief summary of a research article, The development of Islamic banking in Indonesia has shown significant growth, particularly through the implementation of murabahah contracts in financing at Sharia Rural Banks (BPRS). Murabahah is one of the most widely used financing products due to its relatively simple mechanism and ease of understanding by the public. This study aims to analyze the implementation of murabahah contracts in financing at BPRS Alwadiah Tasikmalaya, including the stages of implementation, compliance with sharia principles, and the challenges encountered. The research method used is a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation involving relevant parties at BPRS Alwadiah Tasikmalaya. The results indicate that the implementation of murabahah financing has been carried out systematically, starting from the financing application process, feasibility analysis, purchase of goods by the bank, execution of the contract, and installment payments. In general, the implementation is in accordance with sharia principles, such as price transparency and the absence of riba elements. However, several challenges remain, including the limited understanding of customers, the risk of delayed payments, and the use of wakalah contracts which require proper supervision to ensure compliance with sharia regulations. Overall, the implementation of murabahah financing at BPRS Alwadiah Tasikmalaya has been effectively carried out and is in accordance with sharia principles, although improvements are still needed in customer education and contract supervision.